Kontroversi Mazhab tentang Wakaf uang dan Implikasinya terhadap Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf - Sulfinadia, Hamda (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Endowments money were not only provides a new alternative for Muslims in Indonesia in berwakaf. But also serves to provide a solution for improving the welfare of the wider community. The introduction of cash waqf in the lives of Muslims in Indonesia have shifted he old paradigm. Besides the introduction of this money back waqf has also provided ample opportunity for Muslims from all walks of life to participate ful????ill waqf money though not in large numbers. The conclusions are the First, endowments developed in accordance with the development of society itself or can be said to be associated with social change. Second, the Act perwakafan in Indonesia combines different school a second opinion about the object waqf that includes movable and immovable. Among the moves bendak including cash and precious metals. Third, endowments money can be used as motivation berwakaf for Muslims, various facilities offered in cash waqf, Muslims will more easily give their contribution to the capital endowments without having to wait in a very large number.